1
$\begingroup$

Let $G:c_0\rightarrow\ell_\infty,x\mapsto x$ be the inclusion map. Let $T:c_0\rightarrow {c_0}^{**},x\mapsto\hat{x}$ be the canonical embedding.

We have $\phi^*:{c_0}^{**}\rightarrow\ell_1^*,\lambda\mapsto\lambda\circ\phi$ is an isometric isomorphism and $\varphi^{-1}:{\ell_1}^*\rightarrow\ell_\infty$ is an isometric isomorphism.

I want to show the diagram below commutes. $\require{AMScd}$ $$\begin{CD} c_0 @> G > > \ell_\infty\\ @V T V V @A A \varphi^{-1}A\\ {c_0}^{**} @> >\phi^* > {\ell_1}^* \end{CD}$$

Does it suffice to show that $\varphi^{-1}\circ\phi^*\circ T$ is $G$?

$\endgroup$
  • 4
    $\begingroup$ That is exactly what it means to commute. $\endgroup$ – Prince M May 12 '18 at 4:44
  • $\begingroup$ It just means if you pick an element in the top left corner, it doesn’t matter which route you take to get to the top right corner. $\endgroup$ – Prince M May 12 '18 at 4:45
  • $\begingroup$ Is $\phi : \ell^1 \to c_0$ the standard isometric isomorphism? Also, is $\varphi : \ell^\infty \to (\ell^1)^*$ the standard isometric isomorphism? $\endgroup$ – mechanodroid May 12 '18 at 8:55
1
$\begingroup$

I'm assuming that $\varphi : \ell^\infty \to (\ell^1)^*$ and $\phi : \ell^1 \to (c_0)^*$ are standard isometric isomorphisms.

Since $\varphi : \ell^\infty \to (\ell^1)^*$ is an isometric isomorphism, we can invert that arrow and show that $\varphi \circ G = \phi^* \circ T$ as functions $c_0 \to (\ell^1)^*$.

Therefore, take $x = (x_n)_n \in c_0$ and $y = (y_n)_n \in \ell^1$.

$$(\varphi \circ G)(x)(y) = \varphi(G(x))(y) = \varphi(\underbrace{x}_{\in \ell^\infty})(y) = \sum_{n=1}^\infty x_ny_n$$

because $\varphi(x)$ is a functional on $\ell^1$ acting as $y \mapsto \sum_{n=1}^\infty x_ny_n$.

On the other hand, we have

$$(\phi^* \circ T)(x)(y) = \phi^*(T(x))(y) = \phi^*(\hat{x})(y) = (\hat{x} \circ \phi)(y) = \hat{x}(\phi(y)) = \phi(y)(x) = \sum_{n=1}^\infty x_ny_n$$

because $\phi(y)$ is a functional on $c_0$ acting as $x \mapsto \sum_{n=1}^\infty x_ny_n$.

Therefore $\varphi \circ G = \phi^* \circ T$ so $G = \varphi^{-1} \circ \phi^* \circ T$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.